Vũ Thị Ngọc Hà
Giới thiệu về bản thân
P(x)-Q(x)=(x³-3x²+x+1)-(2x³-x²+3x-4
=x³-3x²+x+1-2x³+x²-3x+4
= -x³-x²-2x+5
b)thay x =1vào P(x)
P(1)=1³-3.1²+1+1
=0
=>x=1 là nghiệm của Q(x)
P(x)-Q(x)=(x³-3x²+x+1)-(2x³-x²+3x-4
=x³-3x²+x+1-2x³+x²-3x+4
= -x³-x²-2x+5
b)thay x =1vào P(x)
P(1)=1³-3.1²+1+1
=0
=>x=1 là nghiệm của Q(x)
P(x)-Q(x)=(x³-3x²+x+1)-(2x³-x²+3x-4
=x³-3x²+x+1-2x³+x²-3x+4
= -x³-x²-2x+5
b)thay x =1vào P(x)
P(1)=1³-3.1²+1+1
=0
=>x=1 là nghiệm của Q(x)
P(x)-Q(x)=(x³-3x²+x+1)-(2x³-x²+3x-4
=x³-3x²+x+1-2x³+x²-3x+4
= -x³-x²-2x+5
b)thay x =1vào P(x)
P(1)=1³-3.1²+1+1
=0
=>x=1 là nghiệm của Q(x)
P(x)-Q(x)=(x³-3x²+x+1)-(2x³-x²+3x-4
=x³-3x²+x+1-2x³+x²-3x+4
= -x³-x²-2x+5
b)thay x =1vào P(x)
P(1)=1³-3.1²+1+1
=0
=>x=1 là nghiệm của Q(x)
P(x)-Q(x)=(x³-3x²+x+1)-(2x³-x²+3x-4
=x³-3x²+x+1-2x³+x²-3x+4
= -x³-x²-2x+5
b)thay x =1vào P(x)
P(1)=1³-3.1²+1+1
=0
=>x=1 là nghiệm của Q(x)
P(x)-Q(x)=(x³-3x²+x+1)-(2x³-x²+3x-4
=x³-3x²+x+1-2x³+x²-3x+4
= -x³-x²-2x+5
b)thay x =1vào P(x)
P(1)=1³-3.1²+1+1
=0
=>x=1 là nghiệm của Q(x)
P(x)-Q(x)=(x³-3x²+x+1)-(2x³-x²+3x-4
=x³-3x²+x+1-2x³+x²-3x+4
= -x³-x²-2x+5
b)thay x =1vào P(x)
P(1)=1³-3.1²+1+1
=0
=>x=1 là nghiệm của Q(x)
P(x)-Q(x)=(x³-3x²+x+1)-(2x³-x²+3x-4
=x³-3x²+x+1-2x³+x²-3x+4
= -x³-x²-2x+5
b)thay x =1vào P(x)
P(1)=1³-3.1²+1+1
=0
=>x=1 là nghiệm của Q(x)
P(x)-Q(x)=(x³-3x²+x+1)-(2x³-x²+3x-4
=x³-3x²+x+1-2x³+x²-3x+4
= -x³-x²-2x+5
b)thay x =1vào P(x)
P(1)=1³-3.1²+1+1
=0
=>x=1 là nghiệm của Q(x)